2013
DOI: 10.1108/17561371311331106
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Lewis: rural‐to‐urban migration with endogenous policy change

Abstract: Purpose -This paper aims to answer the following questions concerning rural-to-urban labor migration in China: What is the impact of discrimination against non-Hukou in urban public service provision? Will such discrimination disappear in the future within the current policy-making framework? What is the result of such an endogenous policy change as far as urbanization and economic growth are concerned? Design/methodology/approach -The authors build a theoretical model of rural-urban migration, taking into acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In the process of urbanization, there is even a status inequality between residents with a local household registration and ATP without a local household registration. Immigrants who are temporary residents are not treated as city residents and have few rights in terms of labour and employment, housing, health services, education, and welfare guarantees [57]. To reach urbanization of the city, the needs of ATP in these areas must be taken into account to achieve the urban integration and community integration of the ATP.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of urbanization, there is even a status inequality between residents with a local household registration and ATP without a local household registration. Immigrants who are temporary residents are not treated as city residents and have few rights in terms of labour and employment, housing, health services, education, and welfare guarantees [57]. To reach urbanization of the city, the needs of ATP in these areas must be taken into account to achieve the urban integration and community integration of the ATP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the level of industrialization exceeded that of urbanization throughout the period, reflecting the characteristic of PRC urbanization lagging behind industrialization. The most important reason for this gap is the institutional barriers that hinder rural-to-urban migration and restrict the access of migrants to public services (Chen et al 2013). In Figure 12, the level of industrialization is measured by the ratio of secondary and tertiary industries' output value to GDP and the level of urbanization measured by the proportion of urban permanent residents.…”
Section: Urbanization and Industrialization In The Prc From 1980mentioning
confidence: 99%
“…With ongoing economic development, the services sector will create more jobs for migrants. When cities need more labor, the social costs of discriminating against migrants in public services become increasingly higher, so policy makers will have to remove the instruments of discrimination and allow in more migrants (Chen et al 2013). Figure 13 shows that, at the city level in 2010, the gap between urbanization and industrialization was negatively related to average wage, which means economic growth can narrow the urbanization-industrialization gap.…”
Section: The Urbanization-industrialization Gap and Average Wage At Tmentioning
confidence: 99%
“…The discriminations related to Hukou in the labor market directly lead to intraurban inequality and social conflicts (Chen and Lu, ). Chen, Liu, and Lu () pointed out that, even if labor market discrimination is removed, Hukou status still leads to inequality in public services, and consequently social conflicts and unproductive waste. Using data from Shanghai, Wang, Chen, and Lu () found that, compared with local residents, migrants have significantly lower trust scores in terms of within‐community trust, social trust and public trust.…”
Section: The Prc's Urbanization and Urban System: Segregation Represmentioning
confidence: 99%